Eksplorasi Etnomatematika Geometri pada Patung Garuda Wisnu Kencana di Bali - Sriyani, Zulaeka Indah; Sari, Audy Friska Arnita; Shilfiana, Alya; Solehuddin, Moh. Sugeng; Sueca, I Gede Maysha (Jurnal Akademik Pendidikan Matematika, 2024)
This study aims to explore the application of ethnomathematics concepts in the geometric elements of the Garuda Wisnu Kencana (GWK) statue in Bali. The research employs a descriptive qualitative method with an ethnographic approach to analyze the relationship between local cultural elements and mathematical concepts, such as proportions, symmetry, and repetitive patterns, applied in the design of this monumental statue. Data were collected through literature studies, direct observations, and documentation, with the researcher serving as the primary instrument. The collected data were analyzed through a process of transforming visual data into text, grouping relevant data, and interpreting the findings to produce a comprehensive description. The results show that the GWK statue represents an outstanding example of integrating art, culture, and mathematics. Geometric principles were utilized to achieve a design that is not only aesthetically pleasing but also functional and rich in Balinese cultural symbolism. This study highlights that ethnomathematics can be an effective approach to understanding and appreciating cultural heritage through a mathematical perspective, providing new insights into how art and architecture reinforce cultural meanings. The urgency of this research lies in its contribution to enriching the understanding of the relationship between local culture and mathematics, as well as laying the foundation for developing educational models that integrate ethnomathematics with traditional art and architecture.